Experience with Hexetidine in Children with Acute Tonsillopharyngitis - O. V. Shamsheva; E. A. Waltz (LLC "Diagnostics and Vaccines", 2016)
We observed 50 children aged 3 to 15 years, admitted to hospital with a diagnosis of acute respiratory disease, occurring in all children with clinical manifestations of acute tonsillopharyngitis, half of the children - with symptoms of rhinitis and laryngotracheitis, tracheobronchitis and bronchitis. In the group of children receiving hexetidine (25) had a significantly faster compared to the control group (25), reducing the duration of symptoms such as redness and pain in the throat. The presence of hexetidine antiviral and antibacterial activity allows the physician to refrain from the immediate purpose of the course of antibiotic therapy, and allows time for her studies.